Simulasi dan Akurasi Numerik Persamaan Gelombang Satu Dimensi Menggunakan Aproksimasi Metode Beda Hingga - Robbaniyyah, Nuzla Af'idatur; Muliyanti, Annisa Sri; Malasso, Dede Ambiya; Pajri, Dwi Hafizatul (Semeton Mathematics Journal, 2024)
The wave equation is a form of partial differential equation that represents physical phenomena on classical physics that are often encountered in everyday life. For example a mechanical waves, such as water waves, sound waves, and seismics waves or light waves. In this research, discussed one-dimensional homogeneous wave equation. Analytical solutions and numerical solutions will be peeled in this research. The numerical solution is approached by using the finite center difference method with an explicit scheme. The solution obtained is simulated with MATLAB software. The results show that the analytical solution has the same pattern as the numerical solution. In other hand, a good level of accuracy was also is obtained using different methods by using a Mean Absolute Percentage Error (MAPE) value of 12%.